The future of electrical power grids: a direction rooted in power electronics - Monteiro, Vítor Duarte Fernandes (2023)
Electrical power grids are changing with a focus on ensuring energy sustainability and enhanced power quality for all sectors. Over the last few decades, there has been a change from a centralized to a decentralized paradigm, which is the consequence of a large-scale incorporation of new electrical technologies and resultant equipment. Considering the foreseeable continuation of changes in electrical power grids, a direction rooted in power electronics with a focus on hybrid AC/DC grids, including the support of solid-state transformers and unified systems, is presented in this paper. Converging on hybrid AC/DC grids, DC grids (structured as unipolar and bipolar) and coupled and decoupled AC configurations are analyzed. On the other hand, in the context of solid-state transformers, feasible structures are analyzed, including the establishment of hybrid AC/DC grids, and the assessment of gains for boosting power quality is presented. Unified power electronics systems are also of fundamental importance when contextualized within the framework of future power grids, presenting higher efficiency, lower power stages, and the possibility of multiple operations to support the main AC grid. In this paper, such subjects are discussed and contextualized within the framework of future power grids, encompassing highly important and modern structures and their associated challenges. Various situations are characterized, revealing a gradual integration of the cited technologies for future power grids, which are also known as smart grids.